1998
DOI: 10.1177/002215549804600907
|View full text |Cite
|
Sign up to set email alerts
|

Human Corneal Epithelial Basement Membrane and Integrin Alterations in Diabetes and Diabetic Retinopathy1

Abstract: SUMMARYCorneas of diabetic patients have abnormal healing and epithelial adhesion, which may be due to alterations of the corneal extracellular matrix (ECM) and basement membrane (BM). To identify such alterations, various ECM and BM components and integrin receptors were studied by immunofluorescence on sections of normal and diabetic human corneas. Age-matched corneas from 15 normal subjects, 10 diabetics without diabetic retinopathy (DR), and 12 diabetics with DR were used. In DR corneas, the composition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
94
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 37 publications
7
94
0
Order By: Relevance
“…The uncontrolled impairment of corneal wound healing increases the susceptibility of corneal ulcer, microbial keratitis, and even perforation. Diabetic corneal pathology always exhibits epithelial basement membrane abnormalities, reduced hemidesmosome density, and delayed wound healing (3,4). However, hyperglycemia also directly impairs the cellular metabolism and causes abnormal changes of corneal epithelium, such as Akt-, epidermal growth factor receptor (EGFR)-, and Sirt1-mediated cell responses to environmental challenges (5)(6)(7).…”
mentioning
confidence: 99%
“…The uncontrolled impairment of corneal wound healing increases the susceptibility of corneal ulcer, microbial keratitis, and even perforation. Diabetic corneal pathology always exhibits epithelial basement membrane abnormalities, reduced hemidesmosome density, and delayed wound healing (3,4). However, hyperglycemia also directly impairs the cellular metabolism and causes abnormal changes of corneal epithelium, such as Akt-, epidermal growth factor receptor (EGFR)-, and Sirt1-mediated cell responses to environmental challenges (5)(6)(7).…”
mentioning
confidence: 99%
“…30 Some studies with fluorophotometry show that this barrier function is weakened in DM leading to an increase in permeability to fluorescein. 30,31 The corneal epithelium in patients with DM exhibits alterations in both cellular components and basal membrane, which could impair the physiology of the corneal epithelial barrier function 32 and cause the cornea to be more vulnerable to foreign pathogens, such as bacteria and fungi.…”
Section: Tear Filmmentioning
confidence: 99%
“…32 Although the cause of theses abnormalities is not clear, some studies suggested that these disorders may be due to altered basal membrane structure and/or epithelial integrin expression, 28,31 increased glycosylation of type IV collagen 32 and fibronectin, abnormal regulation of the synthesis of extracellular matrix, increased IV collagen, and decreased laminin 31 and heparin sulfate. 27 As far as epithelial basal membrane alteration is concerned, people with DM show an accumulation of fibrillar and granular material between the epithelial cells and Bowman's membrane, thickening and multilayering of the basal membrane, 32,33 and accumulation of glycation end products (AGEs).…”
Section: Tear Filmmentioning
confidence: 99%
See 2 more Smart Citations